2022
DOI: 10.1111/1346-8138.16508
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and drug survival of the infliximab biosimilar CT‐P13 in post‐marketing surveillance of Japanese patients with psoriasis

Abstract: Based on extrapolation of similar clinical outcomes in rheumatoid arthritis to the originator infliximab (IFX) in randomized clinical trials, the first biosimilar antibody CT-P13 was approved for the treatment of psoriasis. To evaluate the safety, efficacy, and drug survival of CT-P13 for psoriasis in real-world clinical practice, prospective post-marketing surveillance was conducted in 165 Japanese psoriasis patients. During a 1-year follow-up period, adverse drug reactions (ADRs) occurred in 29 patients (17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Over the 3-year observation period, the development of ADA was detected in 20 patients of cohort 1 (8.5%) vs. 11 patients of cohort 2 (25%). The risk of treatment discontinuation was significantly higher in patients with positive ADA in both cohorts Morita A, 2022 [45] Efficacy (PASI, DLQI, DAS28-CRP) and safety (AEs)…”
Section: Main Outcomes Main Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Over the 3-year observation period, the development of ADA was detected in 20 patients of cohort 1 (8.5%) vs. 11 patients of cohort 2 (25%). The risk of treatment discontinuation was significantly higher in patients with positive ADA in both cohorts Morita A, 2022 [45] Efficacy (PASI, DLQI, DAS28-CRP) and safety (AEs)…”
Section: Main Outcomes Main Resultsmentioning
confidence: 96%
“…Twelve studies [36][37][38][39][40][41][42][43][44][45]47,48] evaluated the effects in terms of the efficacy and safety derived from the switch among infliximab products. Eleven studies were carried out in Europe, while one study was conducted in Japan.…”
Section: Infliximab Switching Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been >90 switching studies performed with biosimilars which have not revealed any significant issues. 13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This continued surveillance must remain a focus of pharmacovigilance programs to monitor biosimilars as they are on the market. 34…”
Section: Introductionmentioning
confidence: 99%
“…There have been >90 switching studies performed with biosimilars which have not revealed any significant issues. 13,16-33…”
Section: Introductionmentioning
confidence: 99%